Recovery of Added-Value Compounds from Orange and Spinach Processing Residues: Green Extraction of Phenolic Compounds and Evaluation of Antioxidant Activity - María Fernanda Montenegro-Landívar; Paulina Tapia-Quirós; Xanel Vecino; Mònica Reig; César Valderrama; Mercè Granados; José Luis Cortina; Javier Saurina (MDPI AG, 2021)
Phenolic compounds recovery by mechanical stirring extraction (MSE) was studied from orange and spinach wastes using water as a solvent. The statistical analysis showed that the highest total polyphenol content (TPC) yield was obtained using 15 min, 70 °C, 1:100 (w/v) solid/solvent ratio and pH 4 for orange; and 5 min, 50 °C, 1:50 (w/v) solid/solvent ratio and pH 6 for spinach. Under these conditions, the TPC was 1 mg gallic acid equivalent (GAE) g−1 fresh weight (fw) and 0.8 mg GAE g−1 fw for orange and spinach, respectively. MSE substantially increased the phenolic compounds yields (1-fold for orange and 2-fold for spinach) compared with ultrasound-assisted extraction. Furthermore, the antioxidant activity of orange and spinach extracts was evaluated using DPPH, FRAP and ABTS. The obtained results pointed out that the evaluated orange and spinach residues provided extracts with antioxidant activity (2.27 mg TE g−1 and 0.04 mg TE g−1, respectively).